Innovation in learning with EBS apps: Enhancing elementary school students’ critical thinking and problem-solving skills - Isrokatun, I.; Hanifah, Nurdinah; Irawati, Riana; Rohman, Yusuf Abdul; Rosmiati, Rosi; Hanum, Citra Bahadur (Edelweiss Applied Science and Technology, 2024)
The rapid technological advancement in the Era of Society 5.0 demands innovative learning methods to enhance elementary students’ critical thinking and problem-solving skills. This study aims to determine the design of the EBS Apps, the responses of elementary school students to the extent of students’ interest in the app, the difficulties and challenges students encounter when using the apps, how the apps train and improve their critical thinking skills , and how the apps train and improve their problem-solving skills. The population of this study consists of all lower-grade elementary school students in Sumedang Regency, West Java, Indonesia. A randomly selected sample includes 35 lower-grade students (20 boys and 15 girls). This study employs experimental method with a one-group pretest-posttest design by using questionnaires and interviews as the instruments. The results of the study indicate that, first, the EBS Apps design features with elements such as a home screen, material and practice questions, settings, and user instructions, and offers three difficulty levels of material, each presenting four situations. Second, students responded to the EBS Apps as a user-friendly application. Third, students were interested in the features of the EBS Apps, such as practice to answer questions. Fourth, students faced various difficulties and challenges while using the EBS Apps. Fifth, there was an increase in critical thinking skills among elementary school students after using the EBS Apps. Sixth, there was an increase in problem-solving skills among elementary school students after using the EBS Apps.